(untitled) (Journal of Plant Disease Sciences, 2025)
Rice (Oryza sativa L.) is one of the extensively paid staple foods for nearly half of the world’s population. Its production and productivity are significantly affected by various biotic and abiotic stresses, with fungal diseases causing major economic losses. One such disease is brown spot, caused by the Deuteromycetes fungus (teleomorph ), which is a significant challenge in all rice-growing regions, accounting for 5-10% yield loss worldwide annually. Given the significance of brown spot disease in rice, the current investigations aimed to know the efficacy of different Bioagents, Fungicides and Botanicals for management of Helminthosporium oryzae In vitro and In vivo evaluations of bioagents revealed that all the and were found to be more effective. and evaluations of fungicides revealed that all the fungicides (Propiconazole 25% EC and Carboxin 37.5% + Thiram 37.5% WP) were found to be more effective. evaluations of botanical garlic were found to be highly effective against brown spots of rice. In this taxation, we have highlighted epidemiology, control measures practiced and several quantitative and qualitative gaps with respect to disease management, which if rectified would lead to a strong impact on crop disease control and the sustainable rice production that are pertinent to the present situation of farmers.